The Meaning of Burning Incense Ritual as a Preservation of Cultural Values and Beliefs of the Community of Nagan Raya-Aceh - Muzakkir Muzakkir; Rena Juliana; Reni Juliani (IJELR: International Journal of Education, Language, and Religion, 2021)
The ritual of burning incense at Gudang Buloh Mosque, which has existed for hundreds of years, is still upheld by the community of Nagan Raya. This ritual is an ancestral tradition from time to time that has been carried out from generation to generation until now it has been developing in some people in the southwest region of Aceh. The purpose of this study was to investigate the meaning of the burning incense ritual at Gudang Buloh Mosque to the people. This research method is qualitative. The researchers went to the site to collect data. After the researchers made observations, received data from various sources, and interviews, the researcher analyzed them to use as study material. The research site is located in the Syeikh Syaikhuna Gudang Buloh mosque, Ujong Pasie village, Kuala district, Nagan Raya Reign, Aceh Province. The results showed that; First, the ritual of burning incense in the mosque, which is a legacy of the past to this day, is still preserved and has even evolved and become the beliefs of some people in and around it. Second, the ritual of burning incense is guided by the Khadam of the mosque to every community who has a desire so that the ceremony is believed to contain sacred values. Third, from the perspective of social communication, the ritual of burning incense is at the same time a process of socialization for the transmission of ancient values that are exalted by society, and through social communication, the consciousness of the community can build a fraternal bond that what the community believes can be achieved. Based on this belief, the ritual of burning incense is maintained.